Application of the heart failure meta-score to predict prognosis in patients with cardiac resynchronization defibrillators. (1st May 2021) - Theuns, Dominic A.M.J.; Schaer, Beat A.; Caliskan, Kadir; Hoeks, Sanne E.; Sticherling, Christian; Yap, Sing-Chien; Alba, Ana Carolina
Abstract: Background: The Heart Failure (HF) Meta-score may be useful in predicting prognosis in patients with primary prevention cardiac resynchronization defibrillators (CRT-D) considering the competing risk of appropriate defibrillator shock versus mortality. Methods: Data from 648 consecutive patients from two centers were used for the evaluation of the performance of the HF Meta-score. The primary endpoint was mortality and the secondary endpoint was time to first appropriate implantable cardioverter-defibrillator (ICD) shock or death without prior appropriate ICD shock. Fine-Gray model was used for competing risk regression analysis. Results: In the entire cohort, 237 patients died over a median follow-up of 5.2 years. Five-year cumulative incidence of mortality ranged from 12% to 53%, for quintiles 1 through 5 of the HF Meta-score, respectively (log-rank P  < 0.001). Compared with the lowest quintile, mortality risk was higher in the highest quintile (HR 6.9; 95%CI 3.7–12.8). The HF Meta-score had excellent calibration, accuracy, and good discrimination in predicting mortality ( C -statistic 0.76 at 1-year and 0.71 at 5-year). The risk of death without appropriate ICD shock was higher in risk quintile 5 compared to quintile 1 (sub HR 5.8; 95%CI 3.1–11.0, P  < 0.001). Conclusions: Our study demonstrated a good ability of the HF Meta-score to predict survival in HF patients treated with CRT-D as primary prevention. The HF Meta-score proved to be useful in identifying a subgroup with a significantly poor prognosis despite a CRT-D. Highlights: The Heart Failure Meta-score reliably predicts survival in patients who received a CRT-D as primary prevention of SCD. The Heart Failure Meta-score is able to discriminate between patients with a low or high risk for mortality The majority of patients died without experiencing an appropriate ICD shock The Heart Failure Meta-score can be used to identify a subgroup with a significantly poor prognosis despite a CRT-D